Functional Studies of Heading Date-Related Gene TaPRR73, a Paralog of Ppd1 in Common Wheat - Zhang, Wenping; Zhao, Guangyao; Gao, Lifeng; Kong, Xiuying; Guo, Zhiai; Wu, Bihua; Jia, Jizeng (Frontiers in Plant Science, 2016)
Photoperiod response-related genes play a crucial role in duration of the plant growth. In this study, we focused on TaPRR73, a paralog of “Green Revolution” gene Ppd1 (TaPRR37). We found that overexpression of the truncated TaPRR73 form lacking part of the N-terminal PR domain in transgenic rice promoted heading under long day conditions. Association analysis in common wheat verified that TaPRR73 was an important agronomic photoperiod response gene that significantly affected heading date and plant height; expression analysis proved that specific alleles of TaPRR73-A1 had highly expressed levels in earlier heading lines; the distribution of haplotypes indicated that one of these alleles had been selected in breeding programs. Our results demonstrated that TaPRR73 contributed to regulation of heading date in wheat and could be useful in wheat breeding and in broadening adaptation of the crop to new regions.